Strategy discovery in professional soccer match data - Van Haaren, J.; Hannosset, S.; Davis, J. (Proceedings of the KDD-16 Workshop on Large-Scale Sports Analytics, 2016)
This paper explores the task of automatic strategy detection from event-stream data collected from professional soccer matches. Concretely, we focus on discovering interesting event sequences that lead to an attempt on goal. We describe a data-driven approach for identifying patterns of movement that account for both spatial and temporal information which represent potential strategies.